Is Emptiness Non-Empty? Jizang’s Conception of Buddha-Nature - Jenny Hung (Religions, 2025)
Jizang (549–623) is regarded as a prominent figure in Sanlun Buddhism (三論宗) and a revitalizer of Nāgārjuna’s Mādhyamaka tradition in China. In this essay, I argue that Jizang’s concept of non-empty Buddha-nature is compatible with the idea of universal emptiness. My argument unfolds in three steps. First, I argue that, for Jizang, Buddha-nature is the Middle Way (zhongdao 中道), which signifies a spiritual state that avoids the extremes of both emptiness and non-emptiness. Next, I explore how and why Jizang believes that Buddha-nature is eternal. I examine Jizang’s notions of intrinsic eternality (dingxing chang 定性常) and conditional eternality (yinyuan chang 因緣常), aiming to demonstrate that his understanding of Buddha-nature as eternal can be framed within the concept of conditional eternality, where Buddha-nature is seen as the objective manifestation of the dharma body. Since this type of eternality aligns with the principle of universal emptiness, Jizang’s assertion that Buddha-nature is eternal is thus compatible with the notion of universal emptiness. Furthermore, I illustrate that Jizang’s theory of eternal Buddha-nature carries practical implications, suggesting that this assertion serves as encouragement rather than being merely an ontological claim.